2019
DOI: 10.1155/2019/5093803
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating MicroRNAs as Novel Potential Biomarkers for Left Ventricular Remodeling in Postinfarction Heart Failure

Abstract: Circulating microRNAs (miRNAs) have been proposed as potential biomarkers for left ventricular remodeling in postinfarction heart failure (HF). However, the diagnostic reproducibility of the use of circulating miRNAs may be affected by the temporal expression of miRNAs following myocardial infarction (MI). In the current study, using a MI-induced HF rat cohort (4-, 8-, and 12-week post-MI groups), we investigated the temporal expression of plasma miRNAs during the development of left ventricular remodeling. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Recent studies have found that cardiomyocyte apoptosis may be a crucial part of HF pathogenesis [5]. Previous studies [6] have shown that cardiomyocyte apoptosis is very obvious in patients with HF. Therefore, it is quite significant to explore the mechanism of cardiomyocyte apoptosis in HF patients and how to prevent it for HF treatment.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies have found that cardiomyocyte apoptosis may be a crucial part of HF pathogenesis [5]. Previous studies [6] have shown that cardiomyocyte apoptosis is very obvious in patients with HF. Therefore, it is quite significant to explore the mechanism of cardiomyocyte apoptosis in HF patients and how to prevent it for HF treatment.…”
Section: Introductionmentioning
confidence: 98%
“…As a non-coding short-chain RNA, miRNA can play a biological regulatory role by combining with target genes. Recently, miRNA has been found to be effective in all kinds of diseases, including cardiovascular diseases [6]. miR-195-5p has been proved to be down-regulated in coronary artery blood flow disorders in the past [7], which suggests that miR-195-5p may be effective in the development and progression of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has suggested that miRNAs can be used as diagnostic and therapeutic markers for AS and that they regulate the pathologies of vascular diseases ( 15 , 16 ). Previous studies have demonstrated that miR-20a-5p is involved in the development of cardiovascular diseases ( 17 , 18 ). Research into the role of miR-20a-5p in ox-LDL-induced HUVECs is not limited.…”
Section: Introductionmentioning
confidence: 99%
“…The targeting interaction relationship between miR-27b-3p and Tgfbr3 appeared in our prediction results, which further indicated that the miR-27b-3p/Tgfbr3 axis may play a significant role in myocardial hypertrophy. The expression level of plasma miR-20a-5p was proportional to the degree of left ventricular remodeling and dilation after myocardial infarction ( Gao et al, 2019 ). The level of miR-342-3p in circulating miRNAs in heart failure model mice was significantly reduced ( Kaneko et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%